Transfers as an effective instrument of public finance resilience - G. R. Sakhapova (Вестник университета)
The article analyses the budgetary provision of the regions in the Volga Federal District. A vertical and horizontal imbalance of budgets has been revealed. Only two regions are not subsidized, with estimated budgetary capacity above the national average. To balance the budget system and strengthen its resistance to crisis phenomena in the economy, the resilience property of public finances was considered. It has been established that one of the instruments of resilience is interbudgetary transfers, the improvement of distribution methods of which makes it possible to increase the flexibility and adaptability of the regional economy in a period of environmental turbulence. The existing models for the use of intergovernmental transfers are identified and considered: 1) the introduction of blocks for the distribution of subsidies into the system of substantiation of budgetary appropriations based on the developed methods, 2) a binary model for managing the socio-economic development of the region, which performs the dual functioning of the transfer mechanism and priorities strategic development. In order to increase the territories resilience, a model for managing the transfer mechanism is proposed, which, unlike the existing ones, provides for taking into account the stage belonging of the territories, the features and patterns characteristic of each stage of the life cycle (four stages: education, development, maturity and decline).